Experimental Exploration of Multi-dimensional Remote Sensing Technology Applied to Target Aviation Search and Rescue. (1st March 2023) - Yao, Dong; Yan, Chunhui; Wang, Hanyu; Meng, Lingtong; Zheng, Yanghao; Cheng, Yanping; Ma, Tianxiang; Gao, Wen; Liang, Chao; Tan, Songnian
Abstract: Optical sensing system is developing from the original intensity image/video sensing mode to multi-dimensional sensing mode, and people pay more and more attention to the spectral characteristics and polarization characteristics of the target. Aviation platform plays an increasingly important role in the search and rescue field based on its unique vision advantages. In this paper, combining the advantages of multi-dimensional perception of optical load with the advantages of aviation platform, a target detection method based on multi-dimensional information is proposed, and aviation experiments are carried out. The experimental results show that the application of multi-dimensional optical information of the target can effectively reduce the background light interference and improve the relative intensity of the target in the image. The experimental results show that the method proposed in this paper is efficient and feasible, and it may be widely used in the field of aviation target search and rescue in the future.